Breadwinning women: Economic contribution of married and cohabiting women to Costa Rican households - Salazar Mayorga, Camila (2017)
This paper analyzes the economic contribution of married and cohabiting women to the household income, in comparison to the income their partners generate, in Costa Rica.  From a perspective of gender roles, human capital theory and female labor participation, this paper examines what variables influence the probability of contribution.  Based on data by the 2014 National Household Survey, this study found that 51% percent of married or cohabiting women do not generate any income, which shows there is an unequal economic relationship in half of Costa Rican households and the males assume the breadwinning role.  Household chores and the number of children reduce the probability of economic contribution.  On the other hand, women with more years of schooling have a higher probability to contribute equally to the couple’s total income.